Prevalence of IgG Autoantibodies against GD3 Ganglioside in Acute Zika Virus Infection - Nico, Dirlei; Conde, Luciana; Rivera-Correa, Juan L.; Vasconcelos-dos-Santos, Andréia; Mesentier-Louro, Louise; Freire-de-Lima, Leonardo; Arruda, Mônica Barcellos; Freire-de-Lima, Celio Geraldo; Ferreira, Orlando da Costa; Lopes Moreira, Maria Elisabeth; Zin, Andrea Araújo; Vasconcelos, Zilton Farias Meira; et al. (Frontiers in Medicine, 2018)
Zika virus disease has become a global health emergency with devastating effects on public health. Recent evidences implicate the virus as an emergent neuropathological agent promoting serious pathologies of the human nervous system that include destructive and malformation consequences such as development of ocular and fetal brain lesions, microcephaly in neonates and Guillain–Barré syndrome in adults. These neurological disorders of both the CNS and peripheral nervous systems is thought to be associated to the neurotropic properties of the virus that has ability to infect neural stem cells as well as peripheral neurons, a hallmark of its pathogenicity. The presence of autoantibodies against gangliosides plays a pivotal role in the etiogenesis of Guillain-Barre syndrome as well as peripheral neuropathies and variety of diseases of the nervous system. Gangliosides are a class of galactose-containing cerebrosides mainly expressed in nervous system tissues playing a critical role in the physiology of neural cells and neurogenesis. Herein, our findings indicate that patients at acute phase of Zika virus infection without any neurological signs show increased levels of IgG autoantibody against GD3 gangliosides, a class of glycolipid found to be highly expressed in neural stem cell acting in their maintenance of the self-renewal cellular capacity. It is possible that a pathological threshold of these antibodies is only acquired in secondary or subsequent infections. In the light of these evidences, we propose that the target of GD3 by autoimmune responses may possibly has an effect in the neuropathy and neurogenesis disorder seen during Zika virus infection.